Failure Mode Analysis of a CNC Machine by FMEA and Grey Relational Analysis Approach: A Multidisciplinary Approach to Failure Mode Analysis of CNC Machines (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Computer numerical controlled (CNC) machines play an important role in the new machining industry product abilities also production become main issues. Therefore, the optimum turning conditions have to be set. Throughout the entire production processes, the product needs to be monitored in order to meet the overall specificationsThe aim of the present work was to depict the importance of failure modes of CNC hydraulic machines for specifying its relation to key competitive factors and performance indicators. Research in the present work has principally addressed technical issues related to failures of the CNC hydraulic machines. The aim of this research was to synthesize the multidisciplinary nature of CNC machine failures from a performance perspective and highlight some of the more important aspects. The method was presented for calculating Risk Priority Number based on FMEA, which can be used to prioritization of failure modes of CNC hydraulic machines. Optimization of various failure modes have been depicted in the present work based on conventional FMEA approach. And further, the calculated values have been optimized by using Grey Relational Analysis Approach (GRA).